Metabolic Disruption by Naturally Occurring Mycotoxins in Circulation: A Focus on Vascular and Bone Homeostasis Dysfunction - Malvandi, Amir Mohammad; Shahba, Sara; Mehrzad, Jalil; Lombardi, Giovanni (Frontiers in Nutrition, 2022)
Naturally occurring food/feed contaminants have become a significant global issue due to animal and human health implications. Despite risk assessments and legislation setpoints on the mycotoxins' levels, exposure to lower amounts occurs, and it might affect cell homeostasis. However, the inflammatory consequences of this possible everyday exposure to toxins on the vascular microenvironment and arterial dysfunction are unexplored in detail. Circulation is the most accessible path for food-borne toxins, and the consequent metabolic and immune shifts affect systemic health, both on vascular apparatus and bone homeostasis. Their oxidative nature makes mycotoxins a plausible underlying source of low-level toxicity in the bone marrow microenvironment and arterial dysfunction. Mycotoxins could also influence the function of cardiomyocytes with possible injury to the heart. Co-occurrence of mycotoxins can modulate the metabolic pathways favoring osteoblast dysfunction and bone health losses. This review provides a novel insight into understanding the complex events of co-exposure to mixed (low levels) mycotoxicosis and subsequent metabolic/immune disruptions contributing to chronic alterations in circulation.